Comparison of Outcomes in Immediate Implant-Based Breast Reconstruction Versus Mastectomy Alone. Issue 1 (February 2018) - Sousa, Janelle; Sood, Ravi; Liu, Daniel; Calhoun, Kristine; Louie, Otway; Neligan, Peter; Said, Hakim; Mathes, David
Objectives: Immediate implant-based techniques are common practice in post-mastectomy breast reconstruction. Previous studies have shown an increased complication rate in the setting of immediate versus delayed, MD reconstruction. We aimed to quantify any additional risk in complications when implant-based immediate breast reconstruction (IBR) is performed versus mastectomy alone. Materials and Methods: We retrospectively reviewed all IBR cases and all mastectomies without reconstruction from 2007 to 2011. Patient characteristics, operative details, and complication rates were reviewed and analyzed. Results: IBR was performed in 315 consecutive women; mastectomy alone was performed in 401 women. Patients undergoing mastectomy alone were more often older, diabetic, and more frequently underwent neoadjuvant chemotherapy or radiation. Overall complications were higher in the IBR group, most commonly reoperation and delayed wound healing. In a multivariate analysis, IBR, increasing age, body mass index, history of radiation therapy, smoking, and nipple-sparing mastectomy were independently associated with increased risk of complications. However, IBR was only independently associated with increased risk of major complications such as reoperation or readmission for intravenous antibiotics, not minor complications. Conclusion: Patients selected for IBR are inherently different than those undergoing mastectomy alone. After adjusting for these differences, the increased risk of complications seen in IBR is moderately increased over the risk of complications in mastectomy alone. The observed increased risk of major complications after IBR is largely due to the aggressive management of complications in the setting of a prosthetic implant. IBR is a safe reconstructive strategy with only a slightly increased risk over mastectomy alone.